A proposed system for using augmented reality technology in actor training - Hayder Jaafar Aldaghlawy (Basrah Arts Journal, 2024)
The Aim of this Article is to propose an innovative system that combines augmented reality technology with actor training methodologies to enhance actors’ skills, emotional depth, and adaptability. By integrating immersive experiences, real-time feedback, and interactive simulations, this approach aims to revolutionize the field of actor education in the evolving landscape of performing arts. AR technology can transform actor education by providing immersive experiences, immediate feedback, and interactive simulations. Augmented reality (AR) technology superimposes virtual information onto the physical environment, creating a dynamic and immersive experience. It enables prompt assessment of performance, augmenting capabilities and tactics. Augmented reality (AR) interactive simulations can improve actor training by fully engaging performers in intricate situations, promoting flexibility and profound emotional expression. The conventional techniques employed in actor training are constrained by various factors, including the absence of fully immersive experiences, constraints on time and financial resources, and the absence of prompt feedback. Integrating augmented reality (AR) and virtual reality (VR) technologies into actor training enhances the training experience by introducing greater dynamism and variety, enhancing overall performance. This novel method of actor education provides fresh prospects for enhancing skills and performance.